Estimation of Levetiracetam in Tablet Dosage Form by RP-HPLC - N. Appala Raju; J. Venkateswara Rao; K. Vanitha Prakash; K. Mukkanti; K. Srinivasu (E-Journal of Chemistry)
A simple, precise, rapid and accurate reverse phase HPLC method developed for the estimation of levetiracetam in tablet dosage form. A Sun Fire C18, 250 x 4.6 mm, 5 μm partical size, with mobile phase consisting of acetonitrile and 0.03 M potassium dihydrogen phosphate (pH adjusted to 3.0 with orthophosphoric acid) in the ratio of 15:85 v/v was used. The flow rate was 1 mL /min and the effluents were monitored at 210 nm. The retention time was 5.53 min. The detector response was linear in the concentration of 20-240 μg/mL. The respective linear regression equation being Y= 22119.684 x 6829.3428. The limit of detection and limit of quantification was 0.16 and 0.5 μg/mL respectively. The percentage assay of levetiracetam was 99.87%. The method was validated by determining its accuracy, precision and system suitability. The results of the study showed that the proposed RP-HPLC method is simple, rapid, precise and accurate, which is useful for the routine determination of levetiracetam in bulk drug and in its pharmaceutical dosage form.